Production and Marketing Process of Radio and Tv . Media Programs - Winda Kustian; Khafita Aini; Maisarah Maisarah; Muridayani Muridayani; Syahrul Afriansyah (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
It is clear in today's modern society that human beings rely heavily on information. Humans require information that is quick, accurate, and trustworthy. This, of course, has a lot to do interacting with the media, both print and electronic. Television and Radio are one of the media that present information quickly. Television and Radio are still considered to be public-favored information and communication media because they play a significant role in the delivery of balanced and acceptable information in society. People use Television and Radio as information media for education, entertainment, control and social glue. Therefore Television and Radio need proper Program Production and Marketing to promote its broadcasts. Marketing is not only needed by products whose benefits can be directly felt. More than that, marketing is also needed by invisible products whose benefits cannot be felt directly but can be felt later. Program Marketing through television media and consists of a wide range of activities such as advertising, online marketing, events, merchandising, podcasts and funding. To support marketing and production performance, this marketing activity aims to obtain funds or funding used during the pre-production, production and post-production periods. From the series of activities that have been carried out, it can be concluded that online marketing through Television and Radio media is considered very relevant for use today in marketing communications that are integrated with other promotional media.